Creative Skills Training Grows an Entrepreneurial Soul at Fatahilah Orphanage Pangkalan Jati, Depok - Anita Nopiyanti; Dahlia Pinem; Fitri Yetty (PT FORMOSA CENDEKIA GLOBAL, 2023)
The goal of this program is to help orphanage kids become more independent and entrepreneurial. These youngsters must be equipped to compete in the expanding industrial technology 4.0 era. To hone talents and prepare them for difficulties outside the orphanage, creative economy training is conducted. This service's methodology is trained in creating accessories and cultivating an entrepreneurial mindset. Their individuality, creativity, and self-confidence are the major objectives. Activities can be carried out using straightforward lectures, real-world examples of successful entrepreneurs, and group instruction in skill development. The kids of the Fatahillah Orphanage showed positive enthusiasm for this exercise. formal, preparing them to become a generation with knowledge, skills, and who has the attitudes and character necessary to effectively contribute to society and the national economy